Uninitialized Reads. - SEACORD, ROBERT C. (Communications of the ACM, 2017)
The article discusses the effects of uninitialized variable reads within the C programming language, with a focus on the different ways the behavior is handled in the C11 and C2X standards of the language. Topics include the impacts of object initialization, indeterminate values, and trap representations on the behavior of programs coded in the C language.